A comprehensive comparison of third generation epidermal growth factor receptor tyrosine kinase inhibitors in the treatment efficacy and adverse events: A Bayesian meta-analysis - Jinyu Yu, PhD; Hanyu Wu, BS; Lu Yang, MD; Wei Liu, PhD; Baoshan Cao, MD; Baosheng Liang, PhD; Yangchun Gu, MD (Global Medical Genetics, 2025)
Background: It is a challenge for clinicians to choose the optimal third generation EGFR-tyrosine kinase inhibitors (EGFR-TKIs) treatment for individual patients. In this meta-analysis we compare the efficacy of five third-generation EGFR-TKIs, as first-line and second-line therapies for non-small cell lung cancer (NSCLC) patients, and their adverse events (AEs). Methods: A Bayesian hierarchical network meta-analysis was conducted to evaluate the hazard ratios (HR) of first-line therapeutic effects and AEs for these third-generation EGFR-TKIs comparing with first-generation EGFR-TKIs. Additionally, a simple comparison analysis was conducted to evaluate second-line therapeutic effects. Results: All third-generation TKIs exhibited superior efficacy compared to Gefitinib in first-line treatment. Furmonertinib achieved the lowest HR in the exon 19 deletions subgroup (HR: 0.35; 95 % CI: 0.23–0.54), while Lazertinib showed the most favorable HR in the exon 21 L858R subgroup (HR: 0.44; 95 % CI: 0.28–0.70) and among patients with brain metastases (HR: 0.33; 95 % CI 0.18–0.59). In the second-line setting, Furmonertinib achieved the highest numerically objective response rate across the overall population (74.0 %; 95 % CI: 68.0–80.0 %) and all evaluated subgroups. Adverse event analysis showed that Furmonertinib had the lowest overall AE incidence, and Lazertinib had the lowest rate of high-grade (≥ grade 3) AEs. Conclusions: All third-generation EGFR-TKIs exhibited favorable efficacy in both first- and second-line settings. Differences in AE profiles were also noted.